30 Risk factors associated with increasing incidence of uterine cancer after correcting for hysterectomy. (13th November 2020) - Liao, C; Tran, K; Richardson, M; Darcy, K; Tian, C; Hamilton, CA; Maxwell, L; Mann, A; Kapp, DS; Chan, JK
Abstract : Objective: To evaluate the demographic factors associated with the increase in incidence of uterine cancer after correcting for hysterectomy. Methods: From 2001–2016, incidence rates of uterine cancers (epithelial carcinoma and sarcomas) were estimated from United States Cancer Statistics after correcting for hysterectomy prevalence based on Behavioral Risk Factor Surveillance System data. SEER*Stat and Joinpoint regression were used to calculate incidence rate (per 100, 000) and average annual percent change (AAPC). Results: Of 720, 984 patients, 78% White, 10% Black, 8% Hispanic, and 3% Asian/Pacific-Islander. After correcting for hysterectomy, the estimated incidence increased from 27.1 to 42/100, 000 women. Over 15 years, the incidence increased from 40.8 to 42.9 with an annual percent increase (AAPC) of 0.5% per year (p<0.05). The 65–69 year old group had the highest incidence (185.4). With respect to race, the highest baseline incidence was in Blacks at 49.5 that increased 2.3% per year (AAPC). Whites had an incidence of 43.6 with an annual percent increase of only 0.4%. The Hispanics had an incidence of 35.0 (AAPC=1.1%), then Asians incidence 24.0 (AAPC=1.3%). The intersectionality of age and race showed that the group with the highest risk was 65–69 year old and Black with an incidence of 281.1 (AAPC=2.3%). Conclusion: The intersectionality of age and race found age 65–69 Black women with the highest incidence of uterine cancer with a six-fold increase compared to the general population, using hysterectomy-corrected data. Further studies are warranted to determine potential genetic, social-determinant, or environment exposures to explain these findings.